Myoblasts With Higher IRS-1 Levels Are Eliminated From the Normal Cell Layer During Differentiation - Okino, Ryosuke; Usui, Ami; Yoneyama, Yosuke; Takahashi, Shin-Ichiro; Hakuno, Fumihiko (Frontiers in Endocrinology, 2020)
Insulin receptor substrate (IRS)-1 is a major substrate of insulin-like growth factor (IGF)-I receptors. It is well known that IGF-I and II play essential roles in myogenesis progression. Herein, we report an unexpected phenomenon that IRS-1-overexpressing L6 myoblasts are eliminated from normal cell layers at the beginning of differentiation. Initially, the IRS protein level and apoptosis were examined during myogenic differentiation in L6 myoblasts. We found that the IRS-1 protein level decreased, whereas active caspase 3 increased around one day after induction of differentiation. The addition of a pan-caspase inhibitor, Z-VAD-FMK, inhibited differentiation-induced suppression of the IRS-1 protein level. Apoptosis was not enhanced in L6 myoblasts stably expressing high levels of IRS-1 (L6-IRS-1). However, when L6-IRS-1 was cultured with control cells (L6-mock), we observed that L6-IRS-1 was eliminated from the cell layer. We have recently reported that, in L6-IRS-1, internalization of the IGF-I receptor was delayed and IGF signal activation was sustained for a longer period than in L6-mock. When cells stably expressing IRS-1 3YA mutant, which could not maintain the IGF signals, were cultured with normal cells, elimination from the cell layer was not detected. These data suggested that the high level of IRS-1 in myoblasts induces elimination from the cell layer due to abnormal sustainment of IGF-I receptor activation.